Observational constraints on the linear fluctuation growth rate - Di Porto, Cinzia; Amendola, Luca (Arxiv, 2007)
Several experiments in the near future will test dark energy through its effects on the linear growth of matter perturbations. It is therefore important to find simple and at the same time general parametrizations of the linear growth rate. We show that a simple fitting formula that generalizes previous expressions reproduces the growth function in models that allow for a growth faster than standard, as for instance in scalar-tensor models. We use data from galaxy and Lyman-$α$ power spectra to constrain the linear growth rate. We find $γ=0.6_{-0.3}^{+0.4}$ for the growth rate index and $η=0.0_{-0.2}^{+0.3}$ for the additional growth parameter we introduce.